2023
DOI: 10.1097/pas.0000000000002032
|View full text |Cite
|
Sign up to set email alerts
|

PRAME Expression in Mucosal Melanoma of the Head and Neck Region

Abstract: PRAME (PReferentially expressed Antigen in MElanoma), a cancer-testis antigen expressed in normal and neoplastic tissues with several functions, proved to be a useful diagnostic tool in the differential diagnosis between benign and malignant melanocytic lesions. The current study aims to perform PRAME stain on a retrospective case series of mucosal melanocytic tumors of the head and neck region to compare 3 different scores and evaluate the most reliable one in this diagnostic set. Immunohistochemical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…In a recent study, 98.1% of all nevi tested lacked PRAME expression, while six nevi showed a focal positivity [ 7 ]. Also, in another study, Ricci and his colleagues found that head and neck mucosal melanomas are characterized by PRAME expression [ 8 ]. In addition, they observed that high PRAME expression was associated with nodular histotype and interestingly, female gender.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, 98.1% of all nevi tested lacked PRAME expression, while six nevi showed a focal positivity [ 7 ]. Also, in another study, Ricci and his colleagues found that head and neck mucosal melanomas are characterized by PRAME expression [ 8 ]. In addition, they observed that high PRAME expression was associated with nodular histotype and interestingly, female gender.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, PRAME is more commonly expressed in malignant mucosal melanocytic lesions and its increased expression is associated with a poor prognosis. This factor appears to be a prognostic indicator independent of other factors, such as NRAS mutations, and its expression does not appear to correlate with the specific location of a malignant mucosal lesion [34,38,39]. PRAME expression is highly sensitive and specific in the context of acral melanomas and is a more predictive diagnostic tool than p16 immunohistochemistry.…”
Section: Prame Expression In Melanocytic Lesionsmentioning
confidence: 95%
“…A study by Ricci et al found that most benign melanocytic lesions of the mucosa of the head and neck do not show positive immunostaining for PRAME. However, a minority of cases show rare positive cells scattered in the lesion without significant changes in the expression intensity or location [38]. On the other hand, a study by Toyama et al reported that most mucosal melanomas express PRAME and a high PRAME expression correlates with a poor prognosis.…”
Section: Prame Expression In Melanocytic Lesionsmentioning
confidence: 99%
“…Recently, PRAME expression has received much attention in some types of malignant tumor as a useful diagnostic marker due to its nature of being a cancer/testis antigen [13]. Notably, malignant melanoma and its mimics represents the most intensively investigated area of PRAME expression [14][15][16][17][18][19][20][21][22][23][24]. Numerous articles have examined the expression profiles of PRAME in malignant melanoma and have demonstrated its diagnostic utility.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous articles have examined the expression profiles of PRAME in malignant melanoma and have demonstrated its diagnostic utility. Specifically, most cases of malignant melanoma exhibited positive immunoreactivity to PRAME; in contrast, most benign melanocytic nevi did not [14][15][16][17][18][19][20][21][22][23][24]. Moreover, PRAME expression has also been reported in various types of malignant tumor, other than malignant melanoma, including myxoid liposarcoma, synovial sarcoma, neuroblastoma, renal cell carcinoma, non-small-cell lung cancer, and thymic cancer [8,13,14,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%